Transformation of acute lymphoblastic leukemia with a precursor B-cell immunophenotype to burkitt's lymphoma: A case report - Masoumeh Jafari; Shahla Ansari Damavandi; Forugh Charmduzi (Babol University of Medical Sciences, 2023)
Background: As a new point, some very rare features can be revealed as initial diagnosis of acute lymphoblastic leukemia (ALL) without any evidence of lymphoma-like behavior which after initial recovery, presents with new evidence of lymphoma. Herein, a case of the immunophenotypes of blast cells in B-cell precursor acute lymphoblastic leukemia originated from MYC gene-related that was evidenced later by burkitt lymphoma feature. Case Presentation: Our case was initially diagnosed as a typical B-cell ALL cells with L1 morphology in peripheral blood smear and bone marrow aspiration that was not recovered and referred again that was finally featured as burkitt's lymphoma with L3 morphological feature. Conclusion: Thus, in the primary diagnosis of B-cell ALL and especially in cases with treatment failure, the final feature of burkitt's lymphoma should be potentially in mind.